Real-Time Monitoring System for Solar Power Plants Using PLC and IoT-Based Architecture - KHOWARIZMI, MUHAMMAD HAEKAL; SETIYONO, SETIYONO (Institut Teknologi Nasional, Bandung, 2025)
Integrating renewable energy systems with digital monitoring platforms has become essential for efficient energy management and fault detection. This research presents the development of a real-time monitoring system for Solar Power Plants (PLTS) by integrating Programmable Logic Controller (PLC) and Internet of Things (IoT) technologies. The system uses voltage and current sensors to collect electrical parameters from solar panels, which are processed via a Haiwell PLC and displayed locally on an HMI. Additionally, data are transmitted to a cloudbased IoT platform using a Wi-Fi module, enabling remote monitoring via dashboards. The system was tested using a solar panel simulator under controlled conditions. The results showed accurate real-time data acquisition with an average deviation below 3% compared to benchmark measurement tools. This low-cost and scalable system demonstrates a practical solution for modernizing solar energy monitoring in small to medium-scale installations.